2011
DOI: 10.1097/iae.0b013e318213618c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Brilliant Blue G, Trypan Blue, and Indocyanine Green Dyes to Assist Internal Limiting Membrane Peeling During Macular Hole Surgery

Abstract: Brilliant blue G was comparable with TB in optimizing visual and functional outcomes, while it was similar to ICG in ease of internal limiting membrane peeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
1
52
0
1
Order By: Relevance
“…Their results showed improved visual acuity in 56-85% of patients. 4,10,15 Ocublue Plus has only been recently used clinically as an adjuvant in macular hole surgery. Its complications are unknown as there have not been any documented preclinical and clinical studies using it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results showed improved visual acuity in 56-85% of patients. 4,10,15 Ocublue Plus has only been recently used clinically as an adjuvant in macular hole surgery. Its complications are unknown as there have not been any documented preclinical and clinical studies using it.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13,14,15 Ocublue Plus has already been widely used clinically but its complications are unknown as there has not been any documented preclinical and clinical studies using it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,24 Possible explanations for poor visual outcomes suggested ICG might alter the cleavage plane to involve the innermost retinal layer, and it might also have phototoxicity or direct toxic effects on the exposed retinal pigment epithelium (RPE) at the base of the macular hole. 6,7 It has been reported that ICG can remain in the eye for several months, and infrared hyperfluorescence from ICG may persist for up to 36 months after ICG-assisted ILM peeling.…”
Section: Discussionmentioning
confidence: 99%
“…12 Since ICG toxicity on RPE may occur right after exposure to the dye, protection of the exposed RPE at the base of the macular hole may be an important issue, and other dyes with greater safety, such as brilliant blue G, may be a better choice. 24 In conclusion, ICG-assisted ILM peeling has anatomical and functional benefits for idiopathic full-thickness macular holes. Autologous serum did not further increase the hole closure rate.…”
Section: Kung and Wumentioning
confidence: 99%